Human naive CD8 T cells down-regulate expression of the WNT pathway transcription factors lymphoid enhancer binding factor 1 and transcription factor 7 (T cell factor-1) following antigen encounter in vitro and in vivo. - Willinger, T; Freeman, T; Herbert, M; Hasegawa, H; Mcmichael, A; Callan, M (2006)
The transcription factors lymphoid enhancer binding factor 1 (LEF1) and transcription factor 7 (TCF7) (T cell factor-1 (TCF-1)) are downstream effectors of the WNT signaling pathway, which is a critical regulator of T cell development in the thymus. In this study, we show that LEF1 and TCF7 (TCF-1) are not only expressed in thymocytes, but also in mature T cells. Our data demonstrate that Ag encounter in vivo and engagement of the TCR or IL-15 receptor in vitro leads to the down-regulation of LEF1 and TCF7 (TCF-1) expression in human naive CD8 T cells. We further show that resting T cells preferentially express inhibitory LEF1 and TCF7 (TCF-1) isoforms and that T cell activation changes the isoform balance in favor of stimulatory TCF7 (TCF-1) isoforms. Altogether, our study suggests that proteins involved in the WNT signaling pathway not only regulate T cell development, but also peripheral T cell differentiation.